Guia de estratégias para profissionais de saúde no cuidado da sexualidade do idoso - Barbosa, Camilla Sandrianny Pereira (2021)
Introduction: The process of getting old is defined by countless biological, psychological and sociocultural changes in the subject and sexuality tracks these changes, being considered an indicator of the quality of life of geriatrics. Objectives: identify in the scientific literature the biological, psicossocial and cultural factors experienced by elderly people in the context of sexuality; verify the experience of the old-aged related to the sexuality in the process of aging; verify the strategies used by the medical care professionals in the care of the sexuality of aged people and elaborate a Strategies guide for health care professionals in the care for elderly sexuality. Methodology: a methodological study constituted by integrative revision, research of field and elaboration of a product. Health care professionals in Basic Units of Care and elderly people participated in this study in the city of Queimadas, state of Paraíba. The data collection was achieved with a questionnaire and a script of a half structured interview. The quantitative data was processed by utilization of Microsoft Excel and the qualitative data by the Iramuteq program. The data supported the elaboration of an educative guide with aid of the CoreIDRAW. Results and Discussion: Of the 16 articles selected, was observed that the major registry of publication in the year of 2018 (31,25%), in the field of Geriatry and Gerontology (37,5%) and Nursery (31,2%), in portuguese language (62,5%) and studies of qualitative nature (68,6%). The analysis of the lexicographic context by the Hierarchical Descending Classification, which retained 71,2% of the material, generated five classes, the first and the fourth referring to the eldery and denominated the Comprehension of the Sexuality (17,5%) and the experience and understanding of sexuality (25,5%), while the second, third and fifth classes refer to the professionals and the struggle to approach sexuality (15,8%); Strategies to approach sexuality (21%) and defining sexuality (20,2%). Of the total of 12 seniors, the gender feminine and masculine were equivalent to 50% each. However, there was a predominance of a age group between 60 and 69 years (58,3%), brown skin (50%), married/stable union (50%), residing with the spouse (66,6%), catholic religion (58,3%), complete elementary school (50%), family income up to a minimum age salary (50%), housewives (41,6%). Of the group of 43 health care professionals, the majority is composed by nurses (65,2%), gender feminine (78,3%), with age between 20 and 39 years (61%), brown skin (60,3%), married/stable union (52%), catholic (69,6%), with sensu post graduation (78,3%) and professional operation time between one and five years (43,3%). The elderly attribute sexuality to talking, dating, marriage, getting pregnant and having kids and the experience of sexuality to the husband, sexual intercourse, pregnancy, contraceptives and medicine. The professionals that report having hardships in face of taboos and prejudice, have little demand of attendance to execute treatment, to inform and to provide guidance. The strategies used in their practices require dialogues, talks, estimules, activities and demonstrations to provoke changes and understanding of the body. Final Considerations: the health care professionals present troubles in bringing the subject with eldely people, needing to widen the qualification in this area. The importance of awareness and information of the elderly population about their needs and anxieties is emphasized in this context. To meet these demands, the guide about the care of elderly was elaborated.